The Greek junta and the international system
1 online resource.
Keywords: "This book examines the international dimensions of the Greek military dictatorship of 1967-74 and uses it as a case study to evaluate the major shifts occurring in the international system during a period of rapid change. The policies of the major nation-states in both East and West were determined by realistic Cold War considerations. At the same time, the Greek junta, a profoundly anti-modernist force, failed to cope with an evolving international agenda and moves towards international cooperation. Denouncing it became a rallying point both for international organizations and for human rights activists, and it enabled the EEC to underscore the notion that democracy was an integral characteristic of the European identity. This volume is an original in-depth study of an under-researched subject and the multiple interactions of a complex era. It is divided into three sections: Part I deals with the interaction of the Colonels with state actors; Part II deals with the responses of international organizations and the rising transnational human rights agenda for which the Greek junta became a totemic rallying point; Part III compares and contrasts the transitions to democracy in Southern Europe, and analyses the different models of transition, region building and how they intersected with attempts to foster a European identity. The Greek dictatorship may have been a parochial military regime, but its rise and fall interacted with significant international trends and can therefore serve as a salient case study for promoting a better understanding of international and European trends during the 1960s and 1970s. This book will be of much interest to students of Cold War studies, international history, foreign policy, transatlantic relations and International Relations, in general."--